(3NdGUI GdJHjGf aj CjeGf GdbQBfs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hGddg GYde Yf Pdc ef aVd GPG WdH Gf jOQc ef jTGA adg s
(3BNQgG (B:s
(3GdJi bGdJ dG jQi ai hSYJi EdG GPG cGf GSJCLQgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B203) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs